Cost-effectiveness of multi-sample National Thalassemia Screening Programme vs. single-sample reflex DNA thalassemia screening in Malaysian schools: a comparative study in Sabah and Sarawak - Abd Rahim, Azrin Syahida; Mohamed, Don Ismail; Zakaria, Zukarnain; Sulaiman, Lokman Hakim; Abd. Rahim, Nour El Huda; Jaafar, Safurah (AME Publishing Company, 2025)
Background: Thalassemia poses a significant health and financial burden in Malaysia, highlighting the need for effective screening strategies to reduce the incidence of severe cases and associated costs. While the National Thalassemia Screening Programme (NTSP) for students has made progress in identifying carriers, challenges persist in preventing dropouts and ensuring timely diagnoses. This study assessed the cost-effectiveness of thalassemia screening and prevalence reduction using the single-sample reflex DNA approach comparing Sabah and Sarawak for Form Four or 16-year-old school adolescents. The existing National Screening approach (P1) uses multi-sample compared to the single-sample reflex DNA approach (P2), considering cost, effectiveness, potential cost savings on treatment expenses, and prevalence reduction.